2005
DOI: 10.1111/j.1399-0012.2005.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus‐associated interstitial pneumonitis in solid organ transplant recipients

Abstract: Sirolimus is a potent immunosuppressive agent used with increasing frequency in solid organ transplantation (SOT). However, it has been associated with rare but devastating pulmonary toxicity. We describe a case of pulmonary toxicity associated with the use of sirolimus in a 64-yr-old heart transplant recipient. We also review all reported cases of sirolimus-associated lung toxicity among SOT recipients in an effort to better understand the pathophysiology, risk factors, and outcomes of this rare but serious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
84
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 16 publications
0
84
2
Order By: Relevance
“…19 The frequency and severity of biochemical abnormalities and nausea, stomatitis, rash, diarrhea, anorexia, and vomiting were consistent with the results of other studies of everolimus monotherapy 12,15 and other mTOR inhibitors, [20][21][22] although the frequency of pneumonitis, both overall and grade 3, was found to be greater than previously reported. Pneumonitis is known to develop in patients treated with mTOR inhibitors in the transplantation setting [23][24][25][26] and has been reported in other studies in cancer patients treated with everolimus 27 and temsirolimus. 28 Among 34 women with metastatic breast cancer who were treated with everolimus on either a daily (10 mg/day) or weekly (70 mg/week) schedule, El-Maraghi et al 27 reported clinical and/or radiologic changes that were consistent with possible interstitial lung disease (ILD) in 15 patients, 4 of whom had grade 2 or 3 changes; 5 patients discontinued therapy because of ILD, and all patients with grade 2 of 3 toxicities were managed successfully with glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…19 The frequency and severity of biochemical abnormalities and nausea, stomatitis, rash, diarrhea, anorexia, and vomiting were consistent with the results of other studies of everolimus monotherapy 12,15 and other mTOR inhibitors, [20][21][22] although the frequency of pneumonitis, both overall and grade 3, was found to be greater than previously reported. Pneumonitis is known to develop in patients treated with mTOR inhibitors in the transplantation setting [23][24][25][26] and has been reported in other studies in cancer patients treated with everolimus 27 and temsirolimus. 28 Among 34 women with metastatic breast cancer who were treated with everolimus on either a daily (10 mg/day) or weekly (70 mg/week) schedule, El-Maraghi et al 27 reported clinical and/or radiologic changes that were consistent with possible interstitial lung disease (ILD) in 15 patients, 4 of whom had grade 2 or 3 changes; 5 patients discontinued therapy because of ILD, and all patients with grade 2 of 3 toxicities were managed successfully with glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…35 These differences may explain certain variations in the safety profiles of the two agents. For example, sirolimus has been associated with the development of pneumonitis following renal transplantation, [56][57][58] which may be a cause of pulmonary fibrosis in later stages of the disease. By contrast, no cases of pneumonitis have been reported in renal-transplant patients receiving everolimus with low-dose CsA.…”
Section: Pharmacokinetics: Safety Considerationsmentioning
confidence: 99%
“…[5][6][7][8] Usually it is reversible, with a 4.8% mortality rate. 8 High SRL levels (415 ng/dl), late drug exposure (that is, switch in therapy) and male gender are the risk factors. 8 The mechanism of SRLassociated pulmonary toxicity is not well understood.…”
mentioning
confidence: 99%
“…8 High SRL levels (415 ng/dl), late drug exposure (that is, switch in therapy) and male gender are the risk factors. 8 The mechanism of SRLassociated pulmonary toxicity is not well understood. Etiologies include dose-dependent or immune-mediated toxicity, and direct drug toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation